Assessing the Practical Cybersecurity Skills Gained Through Criminal Justice Academic Programs to Benefit Security Operations Centers (SOCs) - Lucy Tsado; Jung Seob "Scott" Kim (Journal of Cybersecurity Education, Research & Practice, 2022)
Private-sector and public-sector organizations have increasingly built specific business units for securing company assets, reputation, and lives, known as security operations centers (SOCs). Depending on the organization, these centers may also be referred to as global security operations centers, cybersecurity operations centers, fusion centers, and corporate command centers, among many other names. The concept of centralized function within an organization to improve an organization’s security posture has attracted both the government and the private sectors to either build their own SOCs or hire third-party SOC companies.